Noble metal-modified titania with visible-light activity for the decomposition of microorganisms - Endo, Maya; Wei, Zhishun; Wang, Kunlei; Karabiyik, Baris; Yoshiiri, Kenta; Rokicka, Paulina; Ohtani, Bunsho; Markowska-Szczupak, Agata; Kowalska, Ewa (Beilstein Journal of Nanotechnology, 2018)
Commercial titania photocatalysts were modified with silver and gold by photodeposition, and characterized by diffuse reflectance spectroscopy (DRS), X-ray powder diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and scanning transmission electron microscopy (STEM). It was found that silver co-existed in zero valent (core) and oxidized (shell) forms, whereas gold was mainly zero valent. The obtained noble metal-modified samples were examined with regard to antibacterial (Escherichia coli (E. coli)) and antifungal (Aspergillus niger (A. niger), Aspergillus melleus (A. melleus), Penicillium chrysogenum (P. chrysogenum), Candida albicans (C. albicans)) activity under visible-light irradiation and in the dark using disk diffusion, suspension, colony growth (“poisoned food”) and sporulation methods. It was found that silver-modified titania, besides remarkably high antibacterial activity (inhibition of bacterial proliferation), could also decompose bacterial cells under visible-light irradiation, possibly due to an enhanced generation of reactive oxygen species and the intrinsic properties of silver. Gold-modified samples were almost inactive against bacteria in the dark, whereas significant bactericidal effect under visible-light irradiation suggested that the mechanism of bacteria inactivation was initiated by plasmonic excitation of titania by localized surface plasmon resonance of gold. The antifungal activity tests showed efficient suppression of mycelium growth by bare titania, and suppression of mycotoxin generation and sporulation by gold-modified titania. Although, the growth of fungi was hardly inhibited through disc diffusion (inhibition zones around discs), it indicates that gold does not penetrate into the media, and thus, a good stability of plasmonic photocatalysts has been confirmed. In summary, it was found that silver-modified titania showed superior antibacterial activity, whereas gold-modified samples were very active against fungi, suggesting that bimetallic photocatalysts containing both gold and silver should exhibit excellent antimicrobial properties.
Keywords: antifungal properties; antimicrobial properties; bactericidal effect; noble-metal nanoparticles; plasmonic photocatalysis

(untitled) - Blackman, A. (Rev. Environ. Econ. Policy, 2010)

(untitled) - Blancou, J. (Rev. Sci. Tech. (OIE), 1995)

(untitled) - Yang, H.; Cheng, H. (Sep. Purif. Technol., 2007)

(untitled) - Zhang, L.; Gu, F. X.; Chan, J. M.; Wang, A. Z.; Langer, R. S.; Farokhzad, O. C. (Clin. Pharmacol. Ther. (Hoboken, NJ, U. S.), 2008)

(untitled) - Pradeep, T.; Anshup (Thin Solid Films, 2009)

(untitled) - Qu, X.; Alvarez, P. J. J.; Li, Q. L. (Water Res., 2013)

(untitled) - Arslan, I.; Balcioglu, I. A.; Tuhkanen, T. (Environ. Technol., 1999)

(untitled) - Kowalska, E.; Janczarek, M.; Hupka, J.; Grynkiewicz, M. (Water Sci. Technol., 2004)

(untitled) - Barbeni, M.; Minero, C.; Pelizzetti, E.; Borgarello, E.; Serpone, N. (Chemosphere, 1987)

(untitled) - Artuna, E.; Hupka, J. (Cent. Eur. J. Public Health, 2000)

(untitled) - Mozia, S.; Tomaszewska, M.; Morawski, A. W. (Desalination, 2006)

(untitled) - King, C. H.; Shotts, E. B., Jr; Wooley, R. E.; Porter, K. G. (Appl. Environ. Microbiol., 1988)

(untitled) - Mokrini, A.; Ousse, D.; Esplugas, E. (Water Sci. Technol., 1997)

(untitled) - Tomova, D.; Iliev, V.; Rakovsky, S.; Anachkov, M.; Eliyas, A.; Li Puma, G. (J. Photochem. Photobiol., A, 2012)

(untitled) - Hoffmann, M. R.; Martin, S. T.; Choi, W.; Bahnemann, D. W. (Chem. Rev., 1995)

Aquatic and surface photochemistry - Cunningham, J.; Fox, M. A.; Pelizzetti, E.; Pichat, P.; Serpone, N. (Photocatalytic treatment of waters, 1994)

(untitled) - Duffy, J. E.; Anderson, M. A.; Hill, C. G.; Zeltner, W. A. (Ind. Eng. Chem. Res., 2000)

(untitled) - Sánchez-Oneto, J.; Mancini, F.; Portela, J. R.; Nebot, E.; Cansell, F.; Martínez de la Ossa, E. J. (Chem. Eng. J., 2008)

(untitled) - Legrini, O.; Oliveros, E.; Braun, A. M. (Chem. Rev., 1993)

(untitled) - Malato, S.; Blanco, J.; Richter, C.; Curco, D.; Gimenez, J. (Water Sci. Technol., 1997)

(untitled) - Paz, Y. (Appl. Catal., B, 2010)

(untitled) - Murakami, N.; Kurihara, Y.; Tsubota, T.; Ohno, T. (J. Phys. Chem. C, 2009)

(untitled) - Yang, H. G.; Sun, C. H.; Qiao, S. Z.; Zou, J.; Liu, G.; Smith, S. C.; Cheng, H. M.; Lu, G. Q. (Nature, 2008)

(untitled) - Wu, J.-J.; Yu, C.-C. (J. Phys. Chem. B, 2004)

(untitled) - Janczarek, M.; Kowalska, E.; Ohtani, B. (Chem. Eng. J., 2016)

(untitled) - Wei, Z.; Kowalska, E.; Verrett, J.; Colbeau-Justin, C.; Remita, H.; Ohtani, B. (Nanoscale, 2015)

(untitled) - Kouamé, N. A.; Alaoui, O. T.; Herissan, A.; Larios, E.; José-Yacaman, M.; Etcheberry, A.; Colbeau-Justin, C.; Remita, H. (New J. Chem., 2015)

(untitled) - Jaffrezic-Renault, N.; Pichat, P.; Foissy, A.; Mercier, R. (J. Phys. Chem., 1986)

(untitled) - Ząbek, P.; Eberl, J.; Kisch, H. (Photochem. Photobiol. Sci., 2009)

(untitled) - Janus, M.; Tryba, B.; Inagaki, M.; Morawski, A. W. (Appl. Catal., B: Environ., 2004)

(untitled) - Yang, D.; Sun, Y.; Tong, Z.; Tian, Y.; Li, Y.; Jiang, Z. (J. Phys. Chem. C, 2015)

(untitled) - Chen, Q.; Wu, S.; Xin, Y. (Chem. Eng. J., 2016)

(untitled) - Asahi, R.; Morikawa, T.; Ohwaki, T.; Aoki, K.; Taga, Y. (Science, 2001)

(untitled) - Zaleska, A. (Recent Pat. Eng., 2008)

(untitled) - Ohno, T.; Akiyoshi, M.; Umebayashi, T.; Asai, K.; Mitsui, T.; Matsumura, M. (Appl. Catal., A, 2004)

(untitled) - Dozzi, M. V.; Selli, E. (J. Photochem. Photobiol., C, 2013)

(untitled) - Li, G.; Dimitrijevic, N. M.; Chen, L.; Rajh, T.; Gray, K. A. (J. Phys. Chem. C, 2008)

(untitled) - Marschall, R. (Adv. Funct. Mater., 2014)

(untitled) - Barreca, D.; Fornasiero, P.; Gasparotto, A.; Gombac, V.; Maccato, C.; Montini, T.; Tondello, E. (ChemSusChem, 2009)

(untitled) - Wang, G.; Chen, Q.; Xin, Y.; Liu, Y.; Zang, Z.; Hu, C.; Zhang, B. (Electrochim. Acta, 2016)

(untitled) - Kraeutler, B.; Bard, A. J. (J. Am. Chem. Soc., 1978)

(untitled) - Kowalska, E.; Remita, H.; Colbeau-Justin, C.; Hupka, J.; Belloni, J. (J. Phys. Chem. C, 2008)

(untitled) - Kowalska, E.; Yoshiiri, K.; Wei, Z.; Zheng, S.; Kastl, E.; Remita, H.; Rau, S.; Ohtani, B. (Appl. Catal., B: Environ., 2015)

(untitled) - Tian, Y.; Tatsuma, T. (J. Am. Chem. Soc., 2005)

(untitled) - Verbruggen, S. W.; Keulemans, M.; Goris, B.; Blommaerts, N.; Bals, S.; Martens, J. A.; Lenaerts, S. (Appl. Catal., B, 2016)

(untitled) - Lemire, J. A.; Harrison, J. J.; Turner, R. J. (Nat. Rev. Microbiol., 2013)

(untitled) - Rodríguez-Chueca, J.; Ormad, M. P.; Mosteo, R.; Sarasa, J.; Ovelleiro, J. L. (Water Environ. Res., 2015)

(untitled) - Wei, Z.; Endo, M.; Wang, K.; Charbit, E.; Markowska-Szczupak, A.; Ohtani, B.; Kowalska, E. (Chem. Eng. J., 2017)

(untitled) - Benabbou, A. K.; Derriche, Z.; Felix, C.; Lejeune, P.; Guillard, C. (Appl. Catal., B, 2007)

(untitled) - Guillard, C.; Bui, T.-H.; Felix, C.; Moules, V.; Lina, B.; Lejeune, P. (C. R. Chim., 2008)

(untitled) - Zielińska, A.; Kowalska, E.; Sobczak, J. W.; Łącka, I.; Gazda, M.; Ohtani, B.; Hupka, J.; Zaleska, A. (Sep. Purif. Technol., 2010)

(untitled) - Zielińska-Jurek, A.; Wei, Z.; Wysocka, I.; Szweda, P.; Kowalska, E. (Appl. Surf. Sci., 2015)

(untitled) - Kowalska, E.; Mahaney, O. O. P.; Abe, R.; Ohtani, B. (Phys. Chem. Chem. Phys., 2010)

(untitled) - Kowalska, E.; Wei, Z.; Karabiyik, B.; Herissan, A.; Janczarek, M.; Endo, M.; Markowska-Szczupak, A.; Remita, H.; Ohtani, B. (Catal. Today, 2015)

(untitled) - Min, B. K.; Wallace, W. T.; Goodman, D. W. (Surf. Sci., 2006)

(untitled) - Ohtani, B.; Mahaney, O. O. P.; Amano, F.; Murakami, N.; Abe, R. (J. Adv. Oxid. Technol., 2010)

(untitled) - Zheng, S.; Wang, K.; Wei, Z.; Yoshiiri, K.; Braumuller, M.; Rau, S.; Ohtani, B.; Kowalska, E. (J. Adv. Oxid. Technol., 2016)

(untitled) - Xia, Y.; Xiong, Y.; Lim, B.; Skrabalak, S. E. (Angew. Chem., Int. Ed., 2008)

(untitled) - Wang, G.; Feng, H.; Gao, A.; Hao, Q.; Jin, W.; Peng, X.; Li, W.; Wu, G.; Chu, P. K. (ACS Appl. Mater. Interfaces, 2016)

(untitled) - Zeyons, O.; Thill, A.; Chauvat, F.; Menguy, N.; Cassier-Chauvat, C.; Oréar, C.; Daraspe, J.; Auffan, M.; Rose, J.; Spalla, O. (Nanotoxicology, 2009)

(untitled) - Soloviev, A.; Zholos, A.; Ivanova, I.; Novokhatska, T.; Tishkin, S.; Raevska, A.; StroyukC, A.; Yefanov, V. (Vasc. Pharmacol., 2015)

(untitled) - Chin, C.; Park, Y. S. (Cardiol. Ther., 2016)

(untitled) - Halawani, E. M. (Int. J. Curr. Microbiol. Appl. Sci., 2016)

(untitled) - Wang, L. L.; Hu, C.; Shao, L. Q. (Int. J. Nanomed., 2017)

(untitled) - Cao, H.; Qiao, Y.; Liu, X.; Lu, T.; Cui, T.; Meng, F.; Chu, P. K. (Acta Biomater., 2013)

(untitled) - Mogyorósi, K.; Kmetykó, A.; Czirbus, N.; Veréb, G.; Sipos, P.; Dombi, A. (React. Kinet. Catal. Lett., 2009)

(untitled) - Rtimi, S.; Baghriche, O.; Sanjines, R.; Pulgarin, C.; Bensimon, M.; Kiwi, J. (J. Photochem. Photobiol., A, 2013)

(untitled) - Rtimi, S.; Pascu, M.; Sanjines, R.; Pulgarin, C.; Ben-Simon, M.; Houas, A.; Lavanchy, J.-C.; Kiwi, J. (Appl. Catal., B, 2013)

(untitled) - Markowska-Szczupak, A.; Ulfig, K.; Morawski, A. W. (J. Adv. Oxid. Technol., 2012)

(untitled) - Markowska-Szczupak, A.; Janda, K.; Wang, K.; Morawski, A. W.; Kowalska, E. (Cent. Eur. J. Public Health, 2015)

(untitled) - Auyeung, A.; Casillas-Santana, M. A.; Martínez-Castañón, G. A.; Slavin, Y. N.; Zhao, W.; Asnis, J.; Häfeli, U. O.; Bach, H. (PLoS One, 2017)

(untitled) - Prieto-Mahaney, O.-O.; Murakami, N.; Abe, R.; Ohtani, B. (Chem. Lett., 2009)

(untitled) - Nielsen, K. F. (Fungal Genet. Biol., 2003)

(untitled) - Fargues, J.; Rougier, M.; Goujet, R.; Smits, N.; Coustere, C.; Itier, B. (J. Invertebr. Pathol., 1997)

(untitled) - Willocquet, L.; Colombet, D.; Rougier, M.; Fargues, J.; Clerjeau, M. (Eur. J. Plant Pathol., 1996)

(untitled) - Suberkropp, K. (Can. J. Bot., 1995)

(untitled) - Raffaini, G.; Ganazzoli, F. (Philos. Trans. R. Soc. London, Ser. A, 2012)

(untitled) - Ellingsen, J. E. (Biomaterials, 1991)

(untitled) - Rogawansamy, S.; Gaskin, S.; Taylor, M.; Pisaniello, D. (Int. J. Environ. Res. Public Health, 2015)

(untitled) - Markov, S. L.; Vidaković, A. M. (Acta Period. Technol., 2014)